Value co-creation and perceived value: A customer perspective in the hospitality context - Konstantinos Solakis; Jesús Pe\~na-Vinces; Jesús Manuel López-Bonilla (European Research on Management and Business Economics (ERMBE), 2022)
Using the DART (dialogue, access, risk, and transparency) model as a core framework of value co-creation (VCC), and in the context of hospitality services, this study explores the role VCC might have in customers' perceived value (PV). The study delineates two characteristics of PV - perceived quality and price - as sources for competitive strategy. It attempts to establish the existence of an effect of VCC implementation on these sources of strategy, as well as the intensity of the effect. The study's data were collected via self-administered questionnaires from 484 tourists on their return home. Through structural equation modelling, we tested our research hypotheses. The research results indicate that transparency and risk affect a hotel guest's perceptions of price and quality, while access only determines the quality. Contrary to what we expected, dialogue did not have a positive influence on the perceived price or perceived quality. Finally, the results support the notion that perceived quality affects the perceived price. As a firm-orientated model, the DART model was applied to the customer context for the first time in this study, which contributes to the marketing literature.
Keywords: D9; M310; D460; 650; Hospitality services; Hotels; Perceived price; Perceived quality; Perceived value; Value co-creation